2022
DOI: 10.1002/bse.3221
|View full text |Cite
|
Sign up to set email alerts
|

The added value and differentiation among ESG investment strategies in stock markets

Abstract: Environmental, social, and governance (ESG) investment strategies have garnered increasing attention in stock markets worldwide. The number of related funds and their money inflow, for instance, have more than doubled over the past 3 years. Yet, one fundamental question remains unanswered in the specialized literature: has there been any added value and statistical differentiation among ESG strategies in stock markets? We contribute to this discussion by assessing a range of ESG investment strategies across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Pacelli et al (2022) analyzed the link between the performance and the ESG score of different sectoral portfolios and concluded that sustainable investment performance is still heterogeneous worldwide. Meira et al (2022) assessed ESG strategies worldwide. They reported significant differentiation of the governance factor in every region, while the environmental and social portfolios showed similar risk-return profiles and high levels of correlation.…”
Section: The Investment Performance Of Socially Responsible Stocks An...mentioning
confidence: 99%
“…Pacelli et al (2022) analyzed the link between the performance and the ESG score of different sectoral portfolios and concluded that sustainable investment performance is still heterogeneous worldwide. Meira et al (2022) assessed ESG strategies worldwide. They reported significant differentiation of the governance factor in every region, while the environmental and social portfolios showed similar risk-return profiles and high levels of correlation.…”
Section: The Investment Performance Of Socially Responsible Stocks An...mentioning
confidence: 99%
“…Second, companies with strong ESG records are often viewed as more attractive to investors/creditors and may have an easier time securing external financing. Investors are becoming more focused on ESG performance when considering investment opportunities (Meira et al, 2022). Prioritizing social and environmental issues and taking steps to address them can help to reduce the risk of insider misconduct, as well as provide a more secure and profitable environment for investors/creditors.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…As a result, investor attention affects not only stock market prices but also firms' behavior including managers' strategic decision making (Abramova et al, 2020; Hristov & Appolloni, 2022) and corporate financial reporting (Arya & Mittendorf, 2007). Investor concerns have the potential to transform investor investment in green and low‐carbon energy projects by influencing corporate earnings management (Meira et al, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Third, investors have started to lose trust and confidence in traditional energy firms and shifted their attention towards new energy firms due to the aforementioned green policies and increasing public awareness of environmental protection (Kyaw et al, 2022). Accordingly, investors are gradually divesting from the traditional energy sector and investing in the clean energy sector (Meira et al, 2022; Tian et al, 2022). As such, traditional energy firms have a stronger managerial propensity to adopt earnings management to manipulate investor expectations as a way to fulfill their financing demands and guarantee personal career agenda (Garel et al, 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%